THE IMPACT OF EDUCATIONAL TECHNOLOGIES ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC AND PRIVATE UNIVERSITIES IN LAHORE - Abdul Kareem; Mubbasher Mahmood Tariq; Sana Javaid; Muhammad Waqas Rizvi; Amna Rasheed (International Journal of Contemporary Issues in Social Sciences, 2024)
As the digital environment evolves, the incorporation of technology into education has become a significant element of the learning experience. The present study examines the impact of educational technologies on the academic performance of students at public and private universities. The objective of this study is to shed light on how these technologies influence student academic success across various educational contexts. The inquiry evaluated the use of educational technologies, including online learning platforms, digital resources, and interactive tools, while analyzing their relationship with academic performance. For this purpose, a quantitative research methodology was utilized; employing surveys to collect data from a sample of students from public and private institutions. The results indicated that educational technologies substantially affect students’ academic grades. Both public and private university students reported advantages and benefits related to technology use, such as increased access to learning materials, improved communication with instructors, and enhanced flexibility in their study schedules. It also stressed the importance of ensuring equitable access to technological resources and tools, especially in public universities, to close the digital gap and guarantee that all students can benefit from these tools and resources. This research enriches the ongoing conversation about the role of technology in education, highlighting the potential benefits of enhancing students’ learning experiences and outcomes.